(3EdRGejI GdJYdje aj dHfGf (B: (3GdMGLI Gdi GdJYdje GdQSejs - (3GdeQcR GdJQHhj ddHMhK hGdGfeGA s ((3HjQhJs (3GdeQcR GdJQHhj ddHMhK hGdEfeGAs, 2000)
(3jQej gPG GdJbQjQ Edi GSJcTGa ChVGY GdJYdje GdYGe aj dHfGf dLgI GdGfJSGH GdeOQSj hGdJSqQH hGdJCNQ, ceG dLgI bOQI GSJjYGH GdeOGQS GdbGFeI hChVGY GdgjFI GdJYdjejI ajgG, hcdaI GdJYdje aj GdbWGYjjf GdQSej hGdNGU(B. (3Je GdJQcjR HUhQI NGUI Ydi EHQGR GdGQJHGWGJ GdbGFeI Hjf ChVGY GdJYdje GdYGe hGdChVGY GdGLJeGYjI ddCSQ HgOa JMOjO eSJhi GdELQGAGJ hGdJfXjeGJ hGdJQJjHGJ GdJQHhjI hGdEOGQjI hGdJLgjRjI GdJj jLH GJNGPgG dJCejf aYGdjI CcHQ ddeOGQS GdQSejI(B. (3ESJfOJ GdefgLjI GdeJHYI aj gPG GdJbQjQ Edi eQGLYI GdCHMGK hGdOQGSGJ GdeJYdbI HGdChVGY GdJQHhjI ef fGMjI hEdi fJGFL GdYed GdejOGfj HTcd CSGSj ef fGMjI KGfjI, aGJNPJ YjfI eDdaI ef (B200 (3eOQSI QSejI ef cGaI GdefGWb GddHfGfjI hGdeQGMd GdJYdjejI, h (B7000 (3CSQI eef dOjge ChdGO ehdhOhf aj GdaJQI GdhGbYI Hjf YGe (B1975 (3h(B1995 (3aj GdeMGaXGJ GddHfGfjI GdNeS (B((3HjQhJ, LHd dHfGf, GdTeGd, GdLfhH, GdHbGY(B) (3hqRYJ Ydjge GSJeGQI NGUI(B. (3CXgQJ GdfJGFL GNJdGa fSH GdGfJSGH, GdQShH, GdJCNQ GdOQGSj, hGdJSQH ef GdJYdje aj dHfGf HMSH GdeJZjQGJ GdOjehZQGajI, GdLZQGajI, GdGbJUGOjI, GdLZQGajI(B-(3GdGLJeGYjI(B- (3GdGbJUGOjI, GdJQHhjI, hbWGY GdJYdje(B. (3HMjK GQJaY eYOd GdGfJSGH Edi GdbWGY GdJYdjej GdNGU YfO GdaFGJ GdGLJeGYjI hGdGbJUGOjI GdYdjG, HjfeG GQJaYJ fSH GdJCNQ, GdQShH, hGdJSqQH YfO GdaFGJ GdGbJUGOjI(B-(3GdGLJeGYjI GdOfjG, hHTcd NGU aj bWGY GdJYdje GdQSej(B. (3dYH GdbWGY GdNGU GdOhQ GdCcHQ aj eLGd GdJYdje GdYGe aj GdeQGMd GdGHJOGFjI hGdeJhSWI, aGQJaYJ fSHI GdGfJSGH Gdi GdbWGY GdNGU ZjQ GdeLGfj Ydi MSGH GdbWGY GdNGU GdeLGfj, ajeG GROGOJ CgejI GdbWGY GdQSej aj GdeQMdI GdKGfhjI hHTcd NGU aj GdJYdje GdYGdj, dcf fSHI GdQShH GQJaYJ ebGQfI eY GdeOGQS GdNGUI GdeLGfjI hZjQ GdeLGfjI aj cd GdUaha(B.s
(3GdfhY (B: (3JbQjQs
Keywords: (3GdRGejI GdJYdjes; Compulsory Education; Enseignement Obligatoire; Public Sector; Secteur Public; (3GdJYdje GdQSejs